The use of the mirror in speech therapy - Hamerlińska, Agnieszka; Kieczmer, Julita (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
The article begins the description of the history of a mirror: its origin, creation and use. Then the characteristics of the mirror as a typical element of the speech therapy room equipment were made. The article discusses the issue of its use in the opinion of speech therapists. Speech disorders specialists note that it should be used first of all for people with articulation disorders and less for people with mutism.